Analysis of the Refrigeration Performance and Main Influencing Factors of Multi-stage Thermoelectric Coolers - Niu Bingxuan; Liu Zhijie; Liu Zeyu; Shen Limei; Chen Huanxin (Zhileng xuebao)
At present, only a few studies on multi-stage thermoelectric coolers are available, and reports on the cooling performance of such coolers are not consistent. To study the performance of multi-stage thermoelectric coolers, a multi-physics simulation model of single-stage to six-stage thermoelectric coolers is developed based on the physical parameters of commercial-grade thermoelectric materials in this study, and the accuracy of the model is verified experimentally. In terms of the design of the multi-stage thermoelectric cooler, the influences of the external drive circuit and internal structural parameters on its cooling performance are studied. The results show that when the hot end is 27 °C, the six-stage thermoelectric cooler can obtain the maximum cooling temperature difference of 113.32 °C, 71.84 °C, and 129.78 °C using the electrical series, electrical parallel, and independent power drive circuits, respectively. The optimal applications of different driving circuits are further explored, and the causes for the differences in the cooling performance of the multi-stage thermoelectric coolers under different driving circuits are analyzed. A six-stage thermoelectric cooler is taken as an example, and the influence of the thermoelectric leg height of each stage is explored. The results show that the leg height of the highest stage is the most important factor.